How does Inequality Affect Growth? Evidence from a Panel of Canadian Regions - Marchand, Yannick; Breau, Sébastien; Essletzbichler, Jürgen (Canadian Journal of Regional Science / Revue canadienne des sciences régionales, 2019)
This paper investigates the effects of income inequality on regional economic growth in Canada over the 1981 to 2011 period. Using standard cross-sectional models, the consistent pattern we find is that regions with initially higher levels of inequality do subsequently experience greater average annual growth rates over the long-run. In contrast, the medium-term responses are different. Results from fixed effects models point to a negative relationship between inequality and growth. Moreover, across both types of models, we find significant differences for urban and rural regions.